Impact of advent of electronic information resources on performance of library users. Issue 2 (30th May 2019) - Bhat, Nazir Ahmad
Abstract : Purpose: The purpose of this study is to assess the impact of advent of electronic information resources on "academic and carrier related core aspects of user performance". Design/methodology/approach: Seven sampled agricultural universities across northern India were surveyed personally by the investigator for collecting data about the questions under investigation through a structured questionnaire. The response of the users for each statement under investigation was collected with simple "Yes"/"No" option. The investigator also resorted to the telephonic and e-mail communication to collect prompt response and had a personal interaction with respondents to substantiate the collected responses and remove any ambiguity thereof. Findings: It is found that the majority of respondents are of the opinion that due to advent of e-resources the users' interest in studies has enhanced (62.90 per cent) and that the e-resources have played a significant role in timely completion/submission of their study related assignments (74.30 per cent). It is also evident that a good proportion of respondents agree that the advent of e-resources has laid a positive impact on performance of users in "academic examinations" (50.80 per cent), "competitive examinations" (52.80 per cent), and the "interviews" (46.18 per cent) they face. Statistically, it is also verified that the performance of users with respect to five aspects investigated in this study is significantly associated with advent of e-resources ( p < 0.01), whereas it does not show any association with one aspect i.e. "timely completion of an academic degree". Research limitations/implications: The findings are based on mere opinion of users and need to be verified by devising a well-articulated methodology for verification of the user performance related facts both in print and electronic eras, independent of the users' opinion. Practical implications: The findings of this study shall prompt the budget allocating authorities of the libraries to reformulate their fund allocation policies. Findings of this study shall act as logical basis to enhance budget for improving the volume of e-resources. These also emphasize the fact that a provision of recurring fund needs to be created for facilitating single window based anytime anywhere access to the available e-information base, which may include annual subscription charges for availing (i) proxy software services for remote access and (ii) federated search engine for single window searching. Originality/value: This is first work of its nature in northern Indian agricultural libraries. The findings will be useful for the authorities to decide about the degree of importance the libraries need to endorse with the procurement of information resources in electronic form. The study will really inspire the researchers and librarians to conduct similar studies in other specific domains of knowledge and come out with significant findings and suggestions.